English Teaching-Learning Process At The Eighth Grade Of SMP N 1 Cepogo Boyolali In 2014/2015 Academic Year - Agus Febrian, Dwika, Dr. Dwi Haryanti, M.Hum, Siti Fatimah, S. Pd, M. Hum (2015)
This study is focused on English Teaching-learning Process at the Eighth Grade of SMP N 1 Cepogo Boyolali in 2014/2015 Academic Year. This study is aimed to describe the teaching objective, curriculum, syllabus, the roles of teacher, the roles of students, material, the procedure of English teaching-learning process, the assessment and the problems faced by the teacher and the students in English teaching-learning. This is a descriptive qualitative research. The subject of this study is the eighth grade students of SMP N 1 Cepogo Boyolali. The techniques of collecting data are observation, interview, and documents analysis. The data is analyzed using interactive model, namely the data reduction, the data display, and conclusion. The results of this study are there are two objectives of English teaching in SMP N 1 Cepogo Boyolali. First, the general objective of English teaching-learning process in Junior High School is to improve the students' English ability. It includes four language skills, those are listening, speaking, reading, and writing. Second, the specific objectives are such as in listening, students are expected to be able to identify the detail of information. In speaking, students are expected to be able to make conversation about a fact. In reading, the students are expected to be able to read a functional text orally with good intonation. In writing, the students are expected to be able to identify the use of present continous form and to identify the use of simple past tense. The curriculum is the 2006 curriculum. The syllabus is theme-based syllabus. The teacher's roles are as a monitor, as motivator, as a controller, as a model, as a material developer, and as an evaluator. The students' roles are as listener and performer. The materials are books and cassette or CD. The classroom activities focused on the objectives of English teaching-learning. In assessment, there are three steps. Those are the daily test, mid test and final test. Problems faced by teacher are such as the students of SMP N 1 Cepogo give litle attention to the English teaching-learning process, the teacher has limited time to deliver the material, etc. Problems faced by students are such as English is second language for the students, students have limit vocabulary, etc.